A phenomenological study on factors influencing women of childbearing age in the use of intrauterine devices at Gumawang Community Health Center - Lanida, Bella Putri; Murni, Nani Sari; Suryani, Lilis; Yusnilasari, Yusnilasari (Lentera Perawat, 2025)
Background: The Intrauterine Device (IUD) is one of the most effective long-acting reversible contraceptives, yet its utilization remains low in Indonesia, including at Gumawang Community Health Center, Ogan Komering Ulu Timur District. Predisposing factors such as knowledge, beliefs, and cultural perceptions are believed to contribute to the low uptake of IUDs. Objective: This study aimed to analyze the factors influencing IUD use among women of reproductive age. Methods: A qualitative study with a phenomenological approach was conducted to explore participants’ experiences and perceptions. Data were collected through in-depth interviews and focus group discussions (FGDs) involving 17 informants, including IUD acceptors, non-IUD acceptors, unmet need groups, health workers, and family planning program officers. Data analysis employed reduction, data presentation, and conclusion drawing, supported by source triangulation to ensure trustworthiness. Results: Three major themes emerged: (1) knowledge—variations in understanding IUD definition, duration, benefits, and side effects; (2) beliefs—dominated by fear, shame, and mixed religious views; and (3) culture—community myths and narratives surrounding IUD safety that shape perceptions negatively. These findings demonstrate that misinformation and limited exposure strongly influence decision-making regarding IUD adoption. Conclusion: Knowledge, beliefs, and cultural perceptions significantly affect women’s decisions to use IUDs. Strengthening health education, counseling, and partnerships with community and religious leaders is essential to counter misinformation and improve IUD acceptance.